Plume‐Induced Sinking of Intracontinental Lithospheric Mantle: An Overlooked Mechanism of Subduction Initiation?. (19th February 2021) - Cloetingh, Sierd; Koptev, Alexander; Kovács, István; Gerya, Taras; Beniest, Anouk; Willingshofer, Ernst; Ehlers, Todd A.; Andrić‐Tomašević, Nevena; Botsyun, Svetlana; Eizenhöfer, Paul R.; François, Thomas; Beekman, Fred
Abstract: Although many different mechanisms for subduction initiation have been proposed, only few of them are viable in terms of consistency with observations and reproducibility in numerical experiments. In particular, it has recently been demonstrated that intra‐oceanic subduction triggered by an upwelling mantle plume could greatly contribute to the onset and operation of plate tectonics in the early and, to a lesser degree, modern Earth. On the contrary, the initiation of intra‐continental subduction still remains underappreciated. Here we provide an overview of 1) observational evidence for upwelling of hot mantle material flanked by downgoing proto‐slabs of sinking continental mantle lithosphere, and 2) previously published and new numerical models of plume‐induced subduction initiation. Numerical modeling shows that under the condition of a sufficiently thick (>100 km) continental plate, incipient downthrusting at the level of the lowermost lithospheric mantle can be triggered by plume anomalies of moderate temperatures and without significant strain‐ and/or melt‐related weakening of overlying rocks. This finding is in contrast with the requirements for plume‐induced subduction initiation within oceanic or thinner continental lithosphere. As a result, plume‐lithosphere interactions within continental interiors of Paleozoic‐Proterozoic‐(Archean) platforms are the least demanding (and thus potentially very common) mechanism for initiation of subduction‐like foundering in the Phanerozoic Earth. Our findings are supported by a growing body of new geophysical data collected in various intra‐continental areas. A better understanding of the role of intra‐continental mantle downthrusting and foundering in global plate tectonics and, particularly, in the initiation of "classic" ocean‐continent subduction will benefit from more detailed follow‐up investigations. Plain Language Summary: Subduction zones, areas where tectonic plates sink into the Earth mantle, are a vital component of the plate tectonic cycle and result in the opening and closure of oceans over geologic time. Despite major advances in the study of plate tectonics and geodynamics during the last decades, the causes for triggering subduction are still not well understood. In this paper, we review observations and insights from geodynamic models and show that upwelling inside the mantle (i.e., "mantle plumes or hot spots") offer a viable mechanism that takes lithospheric plates back into the deep mantle, thus initiating subduction. However, subduction initiated by mantle plumes within oceanic tectonic plates has rarely been observed in the Phanerozoic history of Earth (541‐0 Ma). In contrast, thick and old continental segments of tectonic plates appear to provide optimal conditions for their participation in plume‐induced sinking (subduction) into the interior of modern Earth in a mode detectable by geophysical imaging in different regions (Europe, Asia, North America). The role of such intra‐continental mantle sinking in global plate tectonics warrants thorough further examination in forthcoming studies. Key Points: We review insights from observational and numerical modeling studies on plume‐induced sinking of lithospheric mantle Plume‐induced mantle downthrusting within continental interiors and at their rims appears to be much more common than hitherto assumed Plausible consequences of intra‐continental mantle sinking for the operation of plate tectonics require further investigation